Consumo de álcool por adolescentes e sua associação com a densidade dos pontos de venda de bebidas alcoólicas e fatores associados no município de Belo Horizonte - Juliana Gabrielle Martins de Oliveira (2014)
The density of alcohol outlets around adolescents schools can hypothetically be associated with greater consumption of alcohol. The literature lacks scientific evidence on this association. Thus, the aim of this study was to examine whether binge drinking during adolescence was associated with exposure to alcohol outlets around schools (density) , type of school (public or private) and individual factors (gender, education mother and consumption of alcohol by family). This is a cross-sectional study that is part of a longitudinal research developed in the city of Belo Horizonte in the years 2010 and 2012. The baseline sample (2010) was 936 high school students aged 15 to 19 years public and private schools, and the follow up sample consisted of 436 of these students who were aged 17 to 18 years in 2012. A sample of the present study was the follow up sample of the aforementioned longitudinal study in 2012 (436 students from 17 to 19 years old) enrolled in public and private schools in the city of Belo Horizonte - MG. Participants completed a self -administered questionnaire, the Test for Identification of Problems Related to Alcohol Use C (AUDIT C); a form related to sociodemographic questions and alcohol consumption by their families. Data for Geographic Information System (GIS ) were used to calculate the density of the points of sale of alcoholic beverages in a radius of 1 km, around schools participating . For statistical analysis we used the association test chi- square test (p < 0.05), the software ArcView for spatial analysis and the Multilevel Poisson analysis. The prevalence of binge drinking was 39.9 %. The results of the multilevel analysis showed that the density of alcohol outlets around schools students was not associated with binge (PR= 0.06, 95% CI 0.78 to 1.28; p= 0.952), nor as sex ( PR = 1.44 , 95 % CI 0.92 to 1.67 , p = 0.151 ). The consumption of alcohol by mothers was associated with alcohol consumption by adolescents (PR = 3.34 , 95% CI 1.23 to 2.25 , p = 0.001 ) as well as with the type of school (PR = 2.17 95% CI 1.03-1.96 , p = 0.030 ). It is concluded that the prevalence of binge drinking between adolescents students was high and was not associated to the density of alcohol outlets around schools students. However, it was associated to the type of school(public) and the consumption of alcohol by the mother.